Carbon Nanosheets by Morphology‐Retained Carbonization of Two‐Dimensional Assembled Anisotropic Carbon Nanorings. Issue 31 (5th July 2018) - Mori, Taizo; Tanaka, Hiroyuki; Dalui, Amit; Mitoma, Nobuhiko; Suzuki, Kengo; Matsumoto, Mutsuyoshi; Aggarwal, Nikhil; Patnaik, Archita; Acharya, Somobrata; Shrestha, Lok Kumar; Sakamoto, Hirotoshi; Itami, Kenichiro; et al.
Abstract: Two‐dimensional (2D) carbon nanomaterials possessing promising physical and chemical properties find applications in high‐performance energy storage devices and catalysts. However, large‐scale fabrication of 2D carbon nanostructures is based on a few specific carbon templates or precursors and poses a formidable challenge. Now a new bottom‐up method for carbon nanosheet fabrication using a newly designed anisotropic carbon nanoring molecule, CPPhen, is presented. CPPhen was self‐assembled at a dynamic air–water interface with a vortex motion to afford molecular nanosheets, which were then carbonized under inert gas flow. Their nanosheet morphologies were retained after carbonization, which has never been seen for low‐molecular weight compounds. Furthermore, adding pyridine as a nitrogen dopant in the self‐assembly step successfully afforded nitrogen‐doped carbon nanosheets containing mainly pyridinic nitrogen species. Abstract : Nanosheets in a maelstrom : A bottom‐up method for carbon nanosheet fabrication using an anisotropic carbon nanoring molecule, CPPhen was developed. CPPhen was self‐assembled at a dynamic air–water interface with a vortex motion to afford molecular nanosheets, which were then carbonized under an inert gas flow. Their nanosheet morphologies were retained after carbonization.